2003
DOI: 10.1038/sj.bjc.6601032
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and economic benefit of HPV-load testing in follow-up and management of women postcone biopsy for CIN2–3

Abstract: This study aimed to evaluate the clinical and economic implications of integrating human papilloma virus (HPV) load testing into the follow-up and management protocol of women postconisation for high-grade cervical intraepithelial neoplasia (CIN2 -3). We evaluated 130 suitable women: 63 were screened biannually by Pap smears ('conventional approach') and 67 also had HPV-load testing ('HPV approach'). More stringent criteria for undergoing colposcopy or reconisation were observed by the former group compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Depending on the study, patients have been tested for HR-HPV at different times, including immediately after conization, 21 within 6 months after conization, [13][14][15]18,19,22 or at 6 months after conization (Table 2). 16,17 Nobbenhuis et al reported that results were similar at both 3 and 6 months after conization (Table 2). 17 The 2001 American Society for Colposcopy and Cervical Pathology (ASCCP) guidelines recommend that testing be performed at least 6 months after treatment to provide sufficient time for clearance of the HPV infection, and that it can be performed at 12 months after treatment unless a patient has risk factors for persistent/recurrent CIN, such as a large lesion or endocervical extension.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Depending on the study, patients have been tested for HR-HPV at different times, including immediately after conization, 21 within 6 months after conization, [13][14][15]18,19,22 or at 6 months after conization (Table 2). 16,17 Nobbenhuis et al reported that results were similar at both 3 and 6 months after conization (Table 2). 17 The 2001 American Society for Colposcopy and Cervical Pathology (ASCCP) guidelines recommend that testing be performed at least 6 months after treatment to provide sufficient time for clearance of the HPV infection, and that it can be performed at 12 months after treatment unless a patient has risk factors for persistent/recurrent CIN, such as a large lesion or endocervical extension.…”
Section: Discussionmentioning
confidence: 85%
“…The sensitivity, specificity, positive and negative predictive values of HR-HPV testing for detecting persistent or recurrent disease after conization have been reported in several studies (Table 2). [13][14][15][16][17][18][19] In particular, the negative predictive value was found to be very high in all studies. Depending on the study, patients have been tested for HR-HPV at different times, including immediately after conization, 21 within 6 months after conization, [13][14][15]18,19,22 or at 6 months after conization (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We can argue that these patients were unnecessarily exposed to peri-and postoperative morbidity. Some other studies also found a relatively high number of reoperated patients who had no residual/recurrent disease confirmed [4,9]. The decision for a second treatment in our study relied upon cytology and colposcopy protocol, mainly (81.2%) during the first year of follow-up.…”
Section: Discussionmentioning
confidence: 51%